Enhanced enzymatic hydrolysis of corn stover using twin‐screw extrusion under mild conditions. (24th July 2022) - Elalami, Doha; Aouine, Mouna; Monlau, Florian; Guillon, Fabienne; Dumon, Claire; Hernandez Raquet, Guillermina; Barakat, Abdellatif
Abstract: This paper aims to investigate the effect of extrusion at high solid loading on corn stover (CS) properties and its enzymatic hydrolysis. This biomass was extruded under different screw speeds and different solid loadings and the impact of these parameters on the physicochemical properties was evaluated. It was found that lignocellulosic components were not significantly affected by the pretreatment, while the surface area increased with solid loading and rotation speed. Different enzyme cocktails were used for the enzymatic hydrolysis of extruded and untreated CS. Overall, mild twin‐extrusion enhanced the enzymatic hydrolysis of CS through an increase in glucose and xylose yields by 134–212% and 214–294%, respectively, when using Trichoderma longibrachiatum cellulase. The highest sugar content was obtained from CS extruded under 400 g total solids per liter and 200 rpm. The energy efficiency of the pretreatment was also assessed and was found to be maximal at 400 g total solids per liter and 200 rpm. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.